Novel Technology for Image Steganography Based on Multi-level DWT and Block Permutation System - Hussam Abd Ali Darweesh (Journal of Madenat Alelem University College, 2012)
This paper proposes a novel technology for image Cryptography, steganography system and embedded high capacity data at the same time. The proposed technologic first encrypted the information by using Zigzag Order Block Permutation (ZOBP), which divides the image into sub-block of size (8*8), then permutated the Blocks depend on Cipher Key. The permutation blocks pixels by zigzag order. The Encrypted information has been converted by Discrete Wavelet Transform (DWT) series of bits in order to increase the power coefficients. The secret information bits embedded into Binary of the cover image after converted by Multi-level DWT. The secret bits replace by bits in cover coefficients. The image results after Inverse Discrete Wavelet Transformation (IDWT) called stego-image. This embedded information casing statistically significant modification to the cover image. The simulation results calculate Peak Signal to Noise Ratio (PSNR), and Correlation test (Cor) as parameters of robustness, and quality of reconstruct image. The proposed system hides high capacity of data depends on the level of DWT to cover image that hiding Capacity parameter calculated by Bit per Pixel (BPP). The proposed method hidden high capacity information with most security and quilility system. Keywords: Imgesteganography, Image Cryptography, Multi-level Discrete wavelet Transform, Zigzag order Block Permutation (ZOBP), Peak Signal to Noise Ratio (PSNR), Correlation test (Cor.), Bit per pixel (Bpp).